Reforms in The Regions Are The Main Driver Of Sustainable Development And Improving The Well-Being And Economic Status Of The Population As An Example Of The Republic Of Uzbekistan - Muhitovich, Ahmedov Tursun; Tolibjonovna, Tursunova Nazokat (International Journal on Economics, Finance and Sustainable Development (IJEFSD), 2024)
This study examines the role of regional reforms in driving sustainable development and improving economic status and well-being in Uzbekistan, as outlined in the Strategy “Uzbekistan-2030.” Addressing the gaps in socio-economic development across different regions, the study employs a mixed-method approach, combining qualitative analyses of policy impacts with quantitative data on industrial production. Findings highlight significant disparities in economic activities, with some sectors showing robust growth while others lag behind. The results underscore the importance of tailored regional policies that promote economic diversification, infrastructure development, and environmental sustainability. The study’s implications suggest that strategic investments and reforms at the regional level are essential for balanced national development and enhancing overall well-being